Cell-Free Plasma Hemoglobin and Male Gender Are Risk Factors for Acute Kidney Injury in Low Risk Children Undergoing Cardiopulmonary Bypass. Issue 11 (November 2017) - Kim-Campbell, Nahmah; Gretchen, Catherine; Callaway, Clifton; Felmet, Kathryn; Kochanek, Patrick M.; Maul, Timothy; Wearden, Peter; Sharma, Mahesh; Viegas, Melita; Munoz, Ricardo; Gladwin, Mark T.; Bayir, Hülya
Abstract : Objectives: To determine the relationship between the production of cell-free plasma hemoglobin and acute kidney injury in infants and children undergoing cardiopulmonary bypass for cardiac surgery. Design: Prospective observational study. Setting: Twelve-bed cardiac ICU in a university-affiliated children's hospital. Patients: Children were prospectively enrolled during their preoperative outpatient appointment with the following criteria: greater than 1 month to less than 18 years old, procedures requiring cardiopulmonary bypass, no preexisting renal dysfunction. Interventions: None. Measurements and Main Results: Plasma and urine were collected at baseline (in a subset), the beginning and end of cardiopulmonary bypass, and 2 hours and 24 hours after cardiopulmonary bypass in 60 subjects. Levels of plasma hemoglobin increased during cardiopulmonary bypass and were associated ( p < 0.01) with cardiopulmonary bypass duration ( R 2 = 0.22), depletion of haptoglobin at end and 24 hours after cardiopulmonary bypass ( R 2 = 0.12 and 0.15, respectively), lactate dehydrogenase levels at end cardiopulmonary bypass ( R 2 = 0.27), and change in creatinine ( R 2 = 0.12). Forty-three percent of patients developed acute kidney injury. There was an association between plasma hemoglobin level and change in creatinine that varied by age (overall [ R 2 = 0.12; p < 0.01]; in age > 2 yr [ R 2 = 0.22; p < 0.01]; and in < 2 yr [ R 2 = 0.03; p = 0.42]). Change in plasma hemoglobin and male gender were found to be risk factors for acute kidney injury (odds ratio, 1.02 and 3.78, respectively; p < 0.05). Conclusions: Generation of plasma hemoglobin during cardiopulmonary bypass and male gender are associated with subsequent renal dysfunction in low-risk pediatric patients, especially in those older than 2 years. Further studies are needed to determine whether specific subgroups of pediatric patients undergoing cardiopulmonary bypass would benefit from potential treatments for hemolysis and plasma hemoglobin–associated renal dysfunction. Abstract : Supplemental Digital Content is available in the text.